Analysing Sustainable Construction Practices in Developing Countries: Success Stories and Challenges - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma Saleh; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Universitas Katolik Parahyangan, 2025)
This study explores the adoption and implementation of sustainable construction practices in developing countries, focusing on key success factors, challenges, and potential solutions. Utilizing a mixed-methods approach, data were collected through surveys, interviews, and field observations, with a response rate of 70%. The findings revealed that while awareness of sustainable construction practices is relatively high (75% of respondents), their implementation remains limited (45% of projects). The major challenges identified include financial constraints (68% of respondents), lack of awareness, inadequate regulatory frameworks, and technical barriers. Critical success factors for sustainable projects include robust government support, effective stakeholder collaboration, access to innovative financing, and comprehensive capacity-building programs. The study contributes to both academic and practical understanding by providing empirical evidence and actionable insights to enhance the adoption of sustainable construction practices. Recommendations for policymakers, construction professionals, and stakeholders include developing comprehensive sustainability policies, providing financial incentives, strengthening regulatory frameworks, promoting public-private partnerships, and investing in continuous capacity building.